Study on chemical constituents of the lichen Parmotrema sancti-angelii (Lynge) Hale. (Parmeliaceae) - Thu Tram, Nguyen Thi; Tuan, Nguyen Trong; Dam, Nguyen Phuc; Ngoc Van, Nguyen Thi; Hong Thanh, Nguyen Pham (Vietnam Journal of Chemistry, 2016)
Lichens are fungal and algal/cyanobacterial symbioses resulting in the production of specific metabolites. Parmotrema sancti-angelii (Lynge) Hale is a lichen which has not been chemically and biologically studied well. From the lichen collected in Vietnam, colour reactions for identification of lichen substances (+K  red, +P yellow, -C, +KC red ) suggested the presence of quinones, depsides and xanthones containing two free hydroxyl groups in meta-position, depsides and depsidones containing an aldehyde group. Chemical constituent study led to the isolation of three compounds, including methyl β-orcinolcarboxylate (1), salazinic acid (2) and atranorin (3). Their structures were confirmed unambiguously by X-ray diffraction, spectroscopic data and compared with those in references. This is the first report of salazinic acid distribution in such lichen. Keywords. Parmeliaceae, Parmotrema sancti-angelii, X-ray, NMR, salazinic acid.